2022
DOI: 10.1111/ene.15432
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of glycemic gap in patients with spontaneous intracerebral hemorrhage

Abstract: Background and purpose Glycemic gap (GG), as a novel biomarker showing the acute glycemic change after the onset of acute illness, has been found to be associated with adverse outcomes in many diseases. This study aimed to explore the prognostic value of GG on long‐term outcomes of spontaneous intracerebral hemorrhage (sICH). Methods The current study included 528 patients from a multicenter, prospective, consecutive, observational cohort study. Poor clinical outcome was defined as modified Rankin Scale ≥ 3. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…HbA1c is a reliable measure of the mean glucose concentration over the last 3‐ to 4‐months, 19,20 which could recognize occult diabetes. Chu et al analyzed HbA1c values and found that SIH was related to the risk of death and adverse prognosis after ICH 13,46,47 . In this study, we combined the levels of HbA1c and admission glucose, along with DM history to distinguish between SIH and DM and classified patients into four groups: NDN, DN, DH, and SIH, as mentioned previously.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…HbA1c is a reliable measure of the mean glucose concentration over the last 3‐ to 4‐months, 19,20 which could recognize occult diabetes. Chu et al analyzed HbA1c values and found that SIH was related to the risk of death and adverse prognosis after ICH 13,46,47 . In this study, we combined the levels of HbA1c and admission glucose, along with DM history to distinguish between SIH and DM and classified patients into four groups: NDN, DN, DH, and SIH, as mentioned previously.…”
Section: Discussionmentioning
confidence: 92%
“…Chu et al analyzed HbA1c values and found that SIH was related to the risk of death and adverse prognosis after ICH. 13,46,47 In this study, we combined the levels of HbA1c and admission glucose, along with DM history to distinguish between SIH and DM and classified patients into four groups: NDN, DN, DH, and SIH, as mentioned previously. We found that around 1/5 of patients (20.5%) had a history of DM, consistent with a previous report in which 15%-30% of patients with ICH had DM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, insulin resistance could also elevate the serum glucose level 30 . All of the above could exert deleterious effects on the blood–brain barrier and parenchymal cells and then exacerbate the brain injury 23 . Besides, stress‐induced hyperglycemia could interfere with the process of ATP generation by causing calcium influx into mitochondria and downregulate aquaporin‐4 in the brain, leading to brain edema, neuronal apoptosis, and the destruction of the brain–blood barrier 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…The glycemic gap is a surrogate marker calculated by subtracting the HbA1c‐derived estimated average glucose from blood glucose and may reflect glycemic excursion in the acute phase 13 . Prior reports revealed that the glycemic gap was associated with left ventricular systolic dysfunction in patients with myocardial infarction 14 and contributed to poor outcomes in patients with spontaneous intracerebral hemorrhage 15 . Nevertheless, studies evaluating the relationship between the glycemic gap and stroke recurrence regarding DM and AF remain limited at present.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Prior reports revealed that the glycemic gap was associated with left ventricular systolic dysfunction in patients with myocardial infarction 14 and contributed to poor outcomes in patients with spontaneous intracerebral hemorrhage. 15 Nevertheless, studies evaluating the relationship between the glycemic gap and stroke recurrence regarding DM and AF remain limited at present. Hence, this study aimed to explore the correlation between glycemic gap and long‐term stroke recurrence in patients with ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%